BEVACIZUMAB COMBINED WITH IRINOTECAN, 5-FLUOROURACIL AND LEUCOVORIN AS THE FIRST- LINE TREATMENT IN PATIENTS WITH METASTATIC COLORECTAL CARCINOMA - Deyan Davidov (Peytchinski Publishing, 2014)
Objective: Bevacizumab improved survival when added to chemotherapy for patients with metastatic colorectal cancer (mCRC). The aim of this study was to explore the efficacy and safety of Bevacizumab containing chemotherapy regimen in the treatment of patient with mCRC. Methods: From January 2010 to March 2012 twenty two consecutive patients with inoperable mCRC entered the study. Treatment schedule consist of intravenous Irinotecan 180 mg/m2 on day 1, Leucovorin 200 mg/m2 administered as intravenous infusion on day 1 and 2 and 5- Fluorouracil 400 mg/m2 bolus and Bevacizumab 5 mg/kg as an intravenous infusion with repetition every two weeks. Results: Overall response rate was 31,9% with one complete response and six partial responses achieved. The overall survival time was 16,6 months. The main toxicities observed were leukopenia and diarrhea. Conclusions: That data suggest that chemotherapy with Irinotecan/ 5- Fluorouracil/ Leucovorin and Bevacizumab remain reasonable regimen for the treatment of patients with mCRC.